The UBXN-2/p37/p47 adaptors of CDC-48/p97 regulate mitosis by limiting the centrosomal recruitment of Aurora A - Kress, Elsa; Schwager, Francoise; Holtackers, Rene; Seiler, Jonas; Prodon, Francois; Zanin, Esther; Eiteneuer, Annika; Toya, Mika; Sugimoto, Asako; Meyer, Hemmo; Meraldi, Patrick; Gotta, Monica (The Journal of Cell Biology, 2013)
Coordination of cell cycle events in space and time is crucial to achieve a successful cell division. Here, we demonstrate that UBXN-2, a substrate adaptor of the AAA ATPase Cdc48/p97, is required to coordinate centrosome maturation timing with mitosis. In UBXN-2-depleted Caenorhabditis elegans embryos, centrosomes recruited more AIR-1 (Aurora A), matured precociously, and alignment of the mitotic spindle with the axis of polarity was impaired. UBXN-2 and CDC-48 coimmunoprecipitated with AIR-1 and the spindle alignment defect was partially rescued by co-depleting AIR-1, indicating that UBXN-2 controls these processes via AIR-1. Similarly, depletion in human cells of the UBXN-2 orthologues p37/p47 resulted in an accumulation of Aurora A at centrosomes and a delay in centrosome separation. The latter defect was also rescued by inhibiting Aurora A. We therefore postulate that the role of this adaptor in cell cycle regulation is conserved. © 2013 Kress et al.
CRIS-Team Scopus Importer:2021-05-26